2016
DOI: 10.1177/0144598716679962
|View full text |Cite
|
Sign up to set email alerts
|

Light hydrocarbon geochemical characteristics and their application in Upper Paleozoic, Shenmu gas field, Ordos Basin

Abstract: Light hydrocarbon has abundant geochemical information, but there are few studies on it in Shenmu gas field. Taking Upper Paleozoic in Shenmu gas field as an example, authors use gas chromatography technology to study light hydrocarbon systematically. The results show that (1) The Shenmu gas field is mainly coal-derived gas, which is mixed by partial oil-derived gas due to the experiment data. (2) Based on K 1 , K 2 parameter and Halpern star chart, the Upper Paleozoic gas in Shenmu gas field belongs to the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The Ordos Basin can be divided into six tectonic units, i.e. the Yimeng Uplift, Weibei Uplift, Jinxi Fold Belt, Xiyuan Thrust Belt, Yi-Shaan Slope and Tianhuan Depression (Liu et al 2009;Yang et al 2014;Han et al 2017b;Li et al 2017;Shi et al 2019) (Fig. 1).…”
Section: Geologic Settingmentioning
confidence: 99%
“…The Ordos Basin can be divided into six tectonic units, i.e. the Yimeng Uplift, Weibei Uplift, Jinxi Fold Belt, Xiyuan Thrust Belt, Yi-Shaan Slope and Tianhuan Depression (Liu et al 2009;Yang et al 2014;Han et al 2017b;Li et al 2017;Shi et al 2019) (Fig. 1).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Ordos Basin is a superimposed cycle of cratonic basin that is the second largest sedimentary basin in China (Li and Hu, 2010; Wang et al, 2010). According to the structural feature and basement properties, the basin can be broadly subdivided into six major tectonic units that are the Yimeng uplift, Yishan slope, Weibei uplift, western margin thrust belts, Tianhuan depression, and Jixi fold belt (Han et al, 2016; Liu et al, 2015). Ordos Basin has experienced multiple tectonic cycles including Caledonian, Hercynian, Indosinian, Yanshan, and Himalayan cycles (Zhao et al, 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, recent research has suggested that non-karstification-dominated carbonates could be targeted for gas exploration. It is well known that gas released from the overlying coal measures has migrated into the very tops of the karstification-dominated reservoirs and the upper Palaeozoic sandstone reservoirs (Han et al., 2017; He et al., 2005). Recently, a tectonics-driven coal-derived gas lateral migration model proposed that the lower sub-members (M 5 5 , M 5 6 , ……, M 5 10 ) situated east of the Central Paleo-uplift may have been charged from the overlying hydrocarbon kitchen (Li et al., 2017; Liu et al., 2015; Miao et al., 2011; Wei et al., 2017; Yang et al., 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%